2010
DOI: 10.1016/j.jqsrt.2010.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Line positions and energy levels of the 18O substitutions from the HDO/D2O spectra between 5600 and 8800cm−1

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The previous work of Ormsby et al [26] in this region assigns all the D 2 16 O transitions observed here, however for D 2 18 O 174 new assignments were made to complement the work of Mikhailenko et al [25].…”
Section: New Assignmentssupporting
confidence: 51%
See 2 more Smart Citations
“…The previous work of Ormsby et al [26] in this region assigns all the D 2 16 O transitions observed here, however for D 2 18 O 174 new assignments were made to complement the work of Mikhailenko et al [25].…”
Section: New Assignmentssupporting
confidence: 51%
“…[27]. Upper labels could then be found by comparison with the published levels of Mikhailenko et al [25] in many cases. …”
Section: Labellingmentioning
confidence: 86%
See 1 more Smart Citation
“…Recently, an exhaustive analysis of the H 2 18 O, H 2 17 O, HD 16 O, HD 18 O, HD 17 O, and D 2 18 O published rotation-vibrational transitions have been performed, and consistent sets of the experimental energy levels have been derived based on the Rydberg-Ritz principle [1][2][3][4]. Rare isotopic species of the water molecule, like HD 18 O, and, especially, D 2 18 O are much less investigated compared to other more abundant isotopologues.…”
Section: Introductionmentioning
confidence: 99%
“…Rare isotopic species of the water molecule, like HD 18 O, and, especially, D 2 18 O are much less investigated compared to other more abundant isotopologues. Complete list of the available studies can be found in [1,3] for HD 18 O and in [4,5] for D 2 18 O. Even for the lowest vibrational states (0 0 0) and (0 1 0), the experimental sets of rotational energy levels were limited (until recent study for D 2 18 O [5]), by J 6 16 and K a 6 10.…”
Section: Introductionmentioning
confidence: 99%